Predictors of Male Sterilization among Eligible, Modern Method of Family Planning Users in India: Evidence from a Nationwide Survey - Biswas, Bijit; Kumar, Abhishek; Agarwal, Neeraj (Indian Journal of Community Health, 2020)
Background: Male sterilization despite being more cost-effective compared to female sterilization is opted by very few Indian eligible couple as family planning (FP) method. Aims & Objectives: To find out attributes of male sterilization among current eligible modern family planning methods users in India. Material & Methods: It was an observational study, cross-sectional in design based on fourth round of national family health survey (NFHS-4) 2015-16 men’s datasheet. There were in total 112122 data, of which 11772 sample population who had completed their family, been using modern methods of family planning and wife in reproductive age (15-49) were selected for analysis. Results: Among the study subjects, 377(3.2%) underwent male sterilization. In multivariable model those who were residing in southern India; Hindu by religion; scheduled caste (SC)/scheduled tribe (ST) by caste; belonged to lower quintile of wealth index; covered by a health insurance scheme; perceived ?2 children as ideal number of children; husbands not working and employed seasonally/occasionally were more likely to undergo male sterilization adjusted with the age of husband, wife, their place of residence and property ownership status. Conclusion: Male sterilization in the sample population was significantly predicted by the region, religion, ethnicity, socioeconomic status, husbands employment status etc.